DEVELOPMENT OF HEXAPOD MANIPULATOR AS MOTION PLATFORM SYSTEM FOR GENERIC FLIGHT DYNAMICS SIMULATOR - Kurniawan Asalani, Yusuf
Development in aerospace technology increases significantly due to computational technology evolution since the finding of the transistor. This condition establishes the easiness of conducting numerical simulation as a design and analysis tool instead of flying prototype aircraft to observe its characteristics. Therefore, as one of aerospace research institution in Indonesia, ITB-Flight Physics Research Group plans to develop competence related to aircraft simulator technology through several research activities which have been started several years ago. To support that objective, a research in motion cue platform is proposed. This research aims to study the characteristics of the hexapod manipulator as a motion platform which is commonly used in the aerospace field for supporting pilot training and improving aircraft handling quality. In the beginning, the hexapod manipulator equation of motion should be learned and implemented to a simulation platform as a design tool. Newton-Euler approach for the inverse-dynamic analysis of hexapod manipulator which was proposed by Dasgupta [10] is used to develop the equation of motion and its implementation. MATLAB/Simulink is chosen as simulation platform software to conduct numerical simulation. The design process, from mechanical design process up to control law design, can be done using the numerical model. However, that numerical model should be validated first using SimScape which is provided by MATLAB. Validation result shows the numerical model has similar result compared to SimScape model. Afterward, the hexapod manipulator physical model can be constructed by using linear actuator. Lastly, several tests can be done to the system. So, some adjustments can be obtained to make numerical model approach the reality. The test result indicates that the physical model has abled to move in accordance with input trajectory although several errors still occur.